2014
DOI: 10.1371/journal.pone.0094583
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Adipocyte Differentiation by Polybrominated Diphenyl Ethers (PBDEs) in 3T3-L1 Cells

Abstract: Polybrominated diphenyl ethers (PBDEs) are a class of brominated flame retardants that were extensively used in commercial products. PBDEs are ubiquitous environmental contaminants that are both lipophilic and bioaccumulative. Effects of PBDEs on adipogenesis were studied in the 3T3-L1 preadipocyte cell model in the presence and absence of a known adipogenic agent, dexamethasone (DEX). A PBDE mixture designed to mimic body burden of North Americans was tested, in addition to the technical mixture DE-71 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 33 publications
(33 reference statements)
4
34
0
Order By: Relevance
“…Moreover, di(2-ethylhexyl) phthalate (DEHP) or its metabolite mono-(2-ethylhexyl) phthalate (MEHP) increased adipocyte differentiation in 3T3-L1 cells, (142) (115), murine mesenchymal stem cells (44), and in vivo (142) (62). Few human studies have addressed effects of BFRs on obesity and metabolic syndrome; however, adipocyte differentiation was increased by the BFRs PDBE (397) and BDE-47 (185). These findings are supported by a recent study which reported increased body weight of obese mice treated with hexabromocyclododecane (HBCD) (431).…”
Section: Effects Of Pops On At Functionmentioning
confidence: 99%
“…Moreover, di(2-ethylhexyl) phthalate (DEHP) or its metabolite mono-(2-ethylhexyl) phthalate (MEHP) increased adipocyte differentiation in 3T3-L1 cells, (142) (115), murine mesenchymal stem cells (44), and in vivo (142) (62). Few human studies have addressed effects of BFRs on obesity and metabolic syndrome; however, adipocyte differentiation was increased by the BFRs PDBE (397) and BDE-47 (185). These findings are supported by a recent study which reported increased body weight of obese mice treated with hexabromocyclododecane (HBCD) (431).…”
Section: Effects Of Pops On At Functionmentioning
confidence: 99%
“…Some of these chemicals have been previously assessed in 3T3-L1 cells, and agree with our results. BDE-47 has been previously reported to promote a low level of triglyceride accumulation 4648 , chlorpyrifos has previously been demonstrated to increase body weight in vivo but not promote (and perhaps inhibit) differentiation in vitro 49, 50 , triclosan has been demonstrated to inhibit adipogenesis 51 , and fipronil has been demonstrated to exhibit minimal triglyceride accumulation 52 . Previous work has demonstrated a low level of triglyceride accumulation for several parabens 50, 53 , in apparent contrast with our results, though this occurred only at concentrations greater than those we tested.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the lower vapor pressures of nona-and deca-BDEs, they are mostly particle-bound which makes them harder to degrade photochemically (Raff and Hites, 2007). Various equipment containing PBDEs found in the indoor environment are main sources of PBDE emission into the air via volatilization (Tung et al, 2014). The existence of these higher brominated PBDEs in the indoor air is probably attributed to their migration behaviours from outdoors to indoors.…”
Section: Metropolis Areasmentioning
confidence: 99%
“…PBDEs have been regarded as a major concern due to their ubiquitous existence in the environment (e.g., form the source to the surrounding air) and their harmful health effects. They are also highly resistant to biological, chemical, and physical degradation, and tend to bio accumulate easily due to their lipophilic property (Cincinelli et al, 2014;Tung et al, 2014). PBDEs negatively affect the endocrine and reproductive functions of humans most especially in females (Hood, 2006;Shy et al, 2012) and cause neurodevelopmental delays after neonatal ingestion of breast milk with high PBDE level (Lin et al, 2010;Chao et al, 2011;Shy et al, 2011;Gascon et al, 2012;Shy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%